Responses of monosex nile tilapia (Oreochromis niloticus) to intraperitoneal challenge by Streptococcus iniae after vaccination with ghosts of the bacterium - Hossain, M M M; Ehsan, A; Rahman, M A; Chowdhury, M B R; Haq, M (Bangladesh Veterinarian, 2012)
The vaccine potential of Streptococcus iniae ghosts produced by gene E mediated lysis was investigated using tilapia (Oreochromis niloticus). Tilapia immunized with S. iniae ghosts (SIG) and formalin killed S. iniae (FKC) vaccines showed significantly higher serum agglutination titres than control fish. Fish immunized with SIG showed no significant differences with fish immunized with FKC in serum agglutination titres, but showed significantly higher bactericidal activity than fish immunized with FKC. Furthermore, fish immunized with SIG showed higher protection than fish immunized with FKC. As this promising type of a non-living whole cell envelope preparation seems to be favorable over conventional vaccines, we suggest S. iniae ghosts as a new vaccine candidate DOI: http://dx.doi.org/10.3329/bvet.v29i1.11889 Bangl. vet. 2012. Vol. 29, No. 1, 31-37